UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA PADA MASA PANDEMI COVID-19 DI MADRASAH ALIYAH RAUDAH TUAL - Zul Fahmi Fakaubun; Anwar Sa’dullah; Mutiara Sari Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This research was conducted to find out how Pai teachers' efforts in coaching students’ morals. Islamic education is one of the teaching programs that need to be applied in the form of coaching and guidance students to understand, internalize, and practice the Islamic teachings that have been determined. The development has done so the students can become moral, ethical and ethical human beings and conform to the objectives of Islamic education. Moral development is not only with theory but must be practised in daily life. In this study, researchers wanted to find out how the student's morality and the efforts from Pai teachers in overcoming obstacles related to the poor morality of students in school. The method used in this study is a qualitative method using interview, observation and documentation techniques. Once the data is collected, the researchers go through the process of data analysis which is by performing data reduction, data display and the last make the conclusions of the data that has been analyzed.